Nursing Student Lived Experience in Conducting Research Paper at STIKes Wira Medika Bali - NI PUTU RIASTINI; NI KOMANG SUKRAANDINI (Alta Dharma Publisher, 2020)
ABSTRACT Research Paper is a new experience faced by university students. In making a Research Paper , a student often enduring obstacles such as confusion, long permit of the research issue, difficult to find suitable literature, writing errors that make the preparation of Research Paper becomes a little hamper. This study aimed to explored the experience of final semester students in making their Research Paper at STIKES Wira Medika Bali. This study uses a qualitative research method with a descriptive phenomenology approach. Data is conducted by a deep interview with 4 participants which consists of 4 female, aged 22-23 years old from a regular program of S1 Bachelor of Nursing. The results of the interview were analyzed by using Collaizi method (Cresswell 2013). The results of the study obtained 5 themes namely, student comprehension, stundents feeling, obstacles or struggle faced by students, efforts of students and their expectation for making a Research Paper . The results of this theme showed that participants experience obstacles in preparation of final Research Paper such as errors in writing, literature that is difficult to obtained, long permit of research that causing the preparation of Research Paper takes a long time. The conclusion of this study conducted 5 themes that is student comprehension, feeling of student, obstacle and struggle faced by student, effort for making Research Paper and student expectation in making final Research Paper . Students are expected to overcoming their obstacles when they are making their Research Paper . Keywords : Experience, Obstacle, Research Paper